(untitled) (Journal of Universal Science Research, 2023)
Geometry as one of the tools of cognition is widely in demand in various fields and directions. One application of this use is the construction of complex geometric structures. In particular, this is possible based on the guilloche technology, which allows the formation of patterned curves. Based on this, the work discusses some approaches to constructing guilloche rosettes. Complex geometric designs using guilloche are presented. The results are presented in the form of separate figures. Some problematic issues are also discussed.